teta is missing here

Log in to add a comment

teta is missing here

Log in to add a comment

=> (cosec-sin)(sec-cos)=1/(tan-cot)

[:. cosec=1/sin]

[:. sec =1/cos]

=>[1/sin -sin][1/cos -cos] =1/[tan+cot]

when we take lcm we get

=[1--sin2/sin][1-cos2/cos] =[1/tan +cot]

when we divide this with {sin A)*(cos A)} we get

1/[{sin²A/(sin A*cos A)} + {cos²A/(sin A* cos A)}]

1/[(sin A/cos A) + cosA /sin A)] = 1/[tan(A) + cot(A)]

hence we get right side

hope this aswer may help you if so plzzz mark the stars below the answer beside thanks.....